Digital Research Methods for Translation Studies. Julie McDonough Dolmaya. - Fang, Yuhua; Zhou, Jinqiao (Digital Scholarship in the Humanities, 2024)
"Digital Research Methods for Translation Studies" is a comprehensive guidebook that explores the digitization of translation studies (TS) and provides practical insights into conducting digital humanities (DH) research in TS. The book is divided into three sections: data collection and organization, data analysis, and data visualization and dissemination. It covers topics such as research project management, accessing open datasets, web-based data collection, and data analysis tools. The author emphasizes the importance of critical evaluation of digital tools and selecting appropriate methodologies based on research purposes. The book also discusses the visualization and presentation of data, and it is relevant not only to TS researchers but also to scholars in linguistics, cultural studies, and other humanities and social sciences disciplines. While the book is comprehensive, it could benefit from including content on large language models (LLMs) and providing more detailed case studies.